Attitudes towards Footpath Businesses in Nepalgunj - Pokhrel, Lal Mani (Academia Research Journal, 2024)
This research report investigates the attitude towards footpath business and its satisfaction scenario of footpath business of Nepalgunj metropolitan city. The study found that the majority of people have a positive attitude towards footpath business, as it provides a source of income for many people who would otherwise be unemployed. However, there are also some negative perceptions of footpath business, such as that it is unsightly and can be a nuisance. The study also found that the level of satisfaction among footpath businessmen is mixed. Some are satisfied with their income, while others are not. The level of income also varies depending on the type of business and the location. The study concludes that footpath business is an important part of the local economy in Nepalgunj. However, it is important to address the negative perceptions of footpath business and to ensure that footpath businessmen are able to operate safely and legally.